2018
DOI: 10.1093/mnras/sty080
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields driven by tidal mixing in radiative stars

Abstract: Stellar magnetism plays an important role in stellar evolution theory. Approximatively 10 % of observed main sequence (MS) and pre-main-sequence (PMS) radiative stars exhibit surface magnetic fields above the detection limit, raising the question of their origin. These stars host outer radiative envelopes, which are stably stratified. Therefore, they are assumed to be motionless in standard models of stellar structure and evolution. We focus on rapidly rotating, radiative stars which may be prone to the tidal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 167 publications
(212 reference statements)
2
58
0
Order By: Relevance
“…They showed that weak magnetic fields can even favour the small-scale tidal turbulence. Global tidal mixing has also been found in global stratified models (Vidal et al 2018). Thus, we may replace any laminar diffusivity (denoted D) by an effective eddy diffusivity (denoted D t ), induced by the nonlinear tidal flows.…”
Section: Mixing-length Theorymentioning
confidence: 77%
See 2 more Smart Citations
“…They showed that weak magnetic fields can even favour the small-scale tidal turbulence. Global tidal mixing has also been found in global stratified models (Vidal et al 2018). Thus, we may replace any laminar diffusivity (denoted D) by an effective eddy diffusivity (denoted D t ), induced by the nonlinear tidal flows.…”
Section: Mixing-length Theorymentioning
confidence: 77%
“…Tidal instability is intrinsically a local (small scale) instability (Kerswell 2002;Cébron et al 2012b;Barker & Lithwick 2013a,b), but it also exists in global models (e.g. Kerswell 1993a; Grannan et al 2016;Vidal et al 2018). The global stability analysis is beyond the scope of the present study.…”
Section: Short-wavelength Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid interiors of these bodies, be it a surface or a sub-surface ocean, a liquid metallic planetary cores or a stellar interior, are known to be sensitive to tidal excitation which drives a wealth of flows. Tides may play a role in the orbital evolution of planets and stars (Ogilvie & Lin 2004;Goodman & Lackner 2009;Le Bars et al 2010;Barker et al 2016), and in dynamo action and magnetic field generation inside terrestrial planets (Kerswell & Malkus 1998;Le Bars et al 2011;Dwyer et al 2011;Cébron et al 2012a;Le Bars et al 2015;Vidal et al 2018). The tidal excitation of flows is primarily driven by the shape deformation of fluid interiors, combined with non-stationary effects.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of those alternative sources of core turbulence for terrestrial bodies has also been the subject of several studies (e.g., Grannan et al, 2016;Lemasquerier et al, 2017;Seyed-Mahmoud et al, 2004) and has given birth to unconventional scenarios to explain past or existing dynamos: for example, on Io (Kerswell & Malkus, 1998), on Mars (Arkani-Hamed et al, 2008), on the Moon (Dwyer et al, 2011;Le Bars et al, 2011), and on the early Earth (Andrault et al, 2016). However, studies of the dynamo capability of the flows resulting from libration, precession, and tides have been up to now sparse and limited to idealized or simplified configurations: that is, laminar dynamos from the precession base flow (Ernst-Hullermann et al, 2013), dynamos for tidal instability with ad hoc bulk forcing in a spherical domain (Cébron & Hollerbach, 2014;Vidal et al, 2017), laminar dynamos in a spheroidal domain for precession and libration instabilities (Wu & Roberts, 2009 (but see also Guermond et al, 2013), and turbulent dynamos in a spherical domain for precession (Kida & Shimizu, 2011;Lin et al, 2016;Tilgner, 2005Tilgner, , 2007. Relevance to planetary configurations implies considering fully turbulent flows in nonaxisymmetric ellipsoidal geometry, accounting for the static and/or dynamic tidal distortions of the CMB.…”
Section: Introductionmentioning
confidence: 99%